Stallion by starlight - Osborne, Mary Pope; Murdocca, Sal (New York : Random House, 2013)
Travel to Ancient Greece with Jack and Annie as they meet Alexander the Great and help tame his wild stallion
Keywords: Alexander, -- the Great, -- 356 B.C.-323 B.C. -- Juvenile fiction; Alexander, -- the Great, -- 356 B.C.-323 B.C. -- Fiction; Magic -- Juvenile fiction; Time travel -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Horses -- Juvenile fiction; Magic -- Fiction; Time travel -- Fiction; Brothers and sisters -- Fiction; Horses -- Fiction; Adventure stories; Fantasy fiction; Historical fiction